Clinical characteristics and IVIG non-responsiveness in Kawasaki disease in infants aged less than 3 months: a retrospective study - Li, Cancan; Sun, Wenqiang; Wang, Huawei; Zhang, Han; Wu, Zhixin; Li, Wenmei; Zhu, Xueping; Geng, Haifeng (Frontiers in Pediatrics, 2025)
ObjectivesTo investigate the clinical characteristics of Kawasaki disease (KD) in infants under 3 months of age and to identify risk factors for intravenous immunoglobulin (IVIG) resistance.MethodsA retrospective analysis was conducted on infants under 3 months with KD hospitalized at the Children's Hospital of Soochow University from January 2020 to December 2024. Patients were divided into complete KD (cKD) and incomplete KD (iKD) groups based on KD diagnostic criteria. Clinical manifestations, CAL incidence, and IVIG responsiveness were compared. Univariate and multivariate logistic regression identified independent risk factors for IVIG resistance.ResultsA total of 47 infants, mean age 70.78 ± 13.55 days, male-to-female ratio 1.47:1, were included. The CAL incidence was 46.81%, with KD onset showing seasonality, peaking in spring and autumn (61.7%). Of the 47 cases, 24 were cKD and 23 iKD. The iKD group had fewer typical symptoms, lower hemoglobin and hematocrit (P < 0.05), and higher cardiac troponin T (P < 0.05). CAL incidence was higher in iKD (65.2%) compared to cKD (29.2%) (P = 0.013), and IVIG resistance was more frequent in iKD group (26.1% vs. 4.2%, P = 0.048). The IVIG-resistant group had lower rates of Bacille Calmette-Guérin (BCG) scar reactivation, conjunctival hyperemia, and cough, but exhibited longer fever duration, higher CAL and coronary artery aneurysms (CAA) rates, higher iKD proportion, and elevated PLR and systemic immune-inflammation index (SII) (P < 0.05). Multivariate analysis identified PLR ≥ 124.05 as an independent risk factor for IVIG resistance.ConclusionClinical manifestations of KD in infants under 3 months of age are often atypical. Compared with cKD, iKD is associated with a higher risk of coronary artery involvement and IVIG resistance. Elevated PLR may serve as an independent predictor of IVIG resistance in this population.